2022
DOI: 10.1002/jdd.12965
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mindfulness practice in mitigating impostor feelings in dental students

Abstract: This study examined (i) the prevalence of impostor feelings in firstyear dental students, (ii) student perceptions of a mindfulness practice as a tool to cope with impostor feelings, and (iii) students' ability to identify their level of impostor feelings. Methods: Two hundred three D1 students at a single institution participated in a mandatory Mind-Body Wellness Course that included the presentation "Understanding Imposter Phenomenon" (lecture #1) and a second presentation "Impostor Phenomenon and Mindfulnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Mindfulness training and practice have been suggested for dental students and may mitigate feelings of impostor syndrome 19 and stress as well as potentially improve overall student wellness 20 . While two‐thirds of student services officers considered mindfulness programs to be well‐utilized, only a third of the student respondents agreed.…”
Section: Resultsmentioning
confidence: 99%
“…Mindfulness training and practice have been suggested for dental students and may mitigate feelings of impostor syndrome 19 and stress as well as potentially improve overall student wellness 20 . While two‐thirds of student services officers considered mindfulness programs to be well‐utilized, only a third of the student respondents agreed.…”
Section: Resultsmentioning
confidence: 99%
“…Within each of these programs, significant associations were found between IP and psychological distress in health professional students [ 27 ]. More recent studies in first-year dental students found 86 % of students reported feelings of IP r and 51 % were classified as frequent or intense impostors on the Clance Impostor Phenomenon Scale [ 28 ]. In pharmacy and nursing students, moderate to high levels of IP feelings have been recently found [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%